Influence of suction on the properties of two granular road materials - Coronado, Octavio (2005)
The results of an experimental work on two road granular materials are presented, including small strains precision triaxial tests under cyclic loading, large strains triaxial tests with measurement of the negative pore water pressure (suction) and wetting tests. The influence of different initial conditions of density, water content and fines content was studied. The two materials differ by their fine contents (7 % for MHC and 10% for HFC). The specimens are compacted at different water content and at a density corresponding to 97% of the Modified Proctor maximum density. The interpretation of the results, in the quasi-elastic domain, is based on an effective stress analysis that allows to take into account both the effects of total stresses and negative pressure, in the perspective of a more rational design of pavement layers.